THE IMPLEMENTATION OF A GENRE-BASED APPROACH TO IMPROVE THE ENGLISH GRAMMAR MASTERY OF THE FIRST-GRADE STUDENTS OF SMA NEGERI 3 SIDRAP - Js, Nurmulyana; Talib, Ahmad; Tahir, Muh. (Universitas Negeri Makassar, 2022)
The purpose of this study is to find out whether the application of the genre-based approach method improves students' ability to use proper grammar. This study used pre-test and post-test with one class as the subject. The researcher's method of choice was random sampling. There were 34 first-grade students at SMA Negeri 3 Sidrap (X MIPA 1) who were sampled for this study. The researcher informed us about the instruments in the pre-test and post-post using different types of texts. The t-test value of (-10.855) further supported the research findings. The researcher found that the p-value was 0.05 from the t-table of the lesson. This necessitates the use of a genre-based approach to help students with their grammar. In other words, using the genre-based approach method can help first-grade students (X MIPA 1) at SMA Negeri 3 Sidrap improve their grammar skills in terms of proper grammar usage, vocabulary, and comprehensibility.